Site Selection of Kangan Municipal Solid Waste Landfill by Using a Fuzzy Analytic Hierarchy Process (FAHP) and GIS - ّFazel Amiri; Firooz Babaei; Tayebeh Tabatabaie (تحقیقات کاربردی علوم جغرافیایی)
Given the potential negative environmental impacts linked with wild landfills in the central part of the Kangan Region, there is a significant need to accelerate the development of controlled inter-municipal landfills. The study area with daily production of 92 tons of waste, due to lack of recycling equipment and incorrect locating landfill is faced with numerous environmental, health and social problems in open sites and unsafe. This study is aimed at identifying suitable sites for solid waste disposal by considering all essential factors and rating criteria by integrating Fuzzy-AHP and GIS with multi-criteria decision analysis (MCDA) in Kangan county. Standards for siting a landfill formulated by the Environmental Protection Agency (EPA) were employed in this study. The criteria that are considered herein are land use, slope, elevation, distance to drainage, groundwater and dams, distance to faults, soil, geology, distance to the residence and road, industrial and infrastructure accessibility. These criteria were assigned fuzzy membership classes based on their importance in siting a landfill. The fuzzy members of all criteria were overlaid to generate the final landfill site suitability map which was classified into five: not suitable (53.3%), less suitable (39.1%), moderately suitable (5.4%), suitable (1.4%) and highly suitable (0.6%). The Analytical Hierarchy Process (AHP) technique was employed in the selection of the landfill site with reverence to multiple criteria and the fuzzy membership classes in accordance with the standards of the EPA. The results of this research in the management of the urban environment and also in the plans of the optimal disposal of urban solid of this area will be useful.